Employee perceptions on the success factors of Teaming With Passion program in Telekom Malaysia Melaka / Zahidah Zaidi - Zaidi, Zahidah (2012)
An objective for this research is to investigate the relationship between perceived sense of personal competence, affective commitment, satisfaction with organizational members and opportunities to participate in decision making on the success of Teaming With Passion (TWP) program from employees’ perceptions in Telekom Malaysia (TM) Melaka. There are 210 respondents of TM Melaka’s employees were selected. The most challenging phase for organizational change is to change the culture and the mindset of the employees as they are important asset to ensure the organizational success. Thus, it is necessary for top management of TM to ensure that TWP will be successful by investigating what are the success factors of TWP from employees’ perception. The researcher collects a primary data which is questionnaire and secondary data for data sources and for collection method. Descriptive statistics and correlation is being used to analyze the data. The interpretation of result from this study, the researcher found that three factors which are perceived sense of personal competence, satisfaction with organizational members and opportunities to participate in decision making are the success factors of TWP program from employees’ perception in TM Melaka. This study also helps the organization to improve the TWP program by achieving its objectives by initiates several program such as Mentoring Program and Employee Involvement Model. Thus, it is emphasized that there is still a need to conduct additional research to filling the gaps that have not been solved in the current study.